The Different Attitudes of Saudi Arabia and Iran Towards the Palestinian-Israeli Conflict: A National Interest Analysis - Tia Afrilia Afrilia; Ahmad Sahide (LPPM Institut Pendidikan Nusantara Global, 2026)
The re-escalation of the Palestine-Israel conflict in 2023 has triggered mixed responses from regional countries, especially Saudi Arabia and Iran, two major powers in the Middle East with contrasting political orientations and national interests. This study aims to analyze the geopolitical dynamics influencing the attitudes of the two countries toward the conflict, using Donald E. Nuechterlein's theory of national interest. Through the library research method, this study identifies that Saudi Arabia tends to emphasize regional stability and maintain strategic relations with the West, while Iran uses the conflict to strengthen its anti-Zionist ideological narrative and expand its regional influence through alliances with non-state actors. The findings show that differences in interests in terms of defense, economy, ideology, and global position significantly shape each country's response patterns. This study contributes to the understanding of the shifting balance of power in the Middle East and the relevance of national interests in determining the direction of foreign policy in the region.